Loss of Mitochondrial Membrane Potential Triggers the Retrograde Response Extending Yeast Replicative Lifespan - Miceli, Michael V.; Jiang, James C.; Tiwari, Anurag; Rodriguez-Quiñones, Jose F.; Jazwinski, S. Michal (Frontiers in Genetics, 2012)
In the budding yeast Sacchoromyces cerevisiae, loss of mitochondrial DNA (rho0) can induce the retrograde response under appropriate conditions, resulting in increased replicative lifespan (RLS). Although the retrograde pathway has been extensively elaborated, the nature of the mitochondrial signal triggering this response has not been clear. Mitochondrial membrane potential (MMP) was severely reduced in rho0 compared to rho+ cells, and RLS was concomitantly extended. To examine the role of MMP in the retrograde response, MMP was increased in the rho0 strain by introducing a mutation in the ATP1 gene, and it was decreased in rho+ cells by deletion of COX4. The ATP1-111 mutation in rho0 cells partially restored the MMP and reduced mean RLS to that of rho+ cells. COX4 deletion decreased MMP in rho+ cells to a value intermediate between rho+ and rho0 cells and similarly increased RLS. The increase in expression of CIT2, the diagnostic gene for the retrograde response, seen in rho0 cells, was substantially suppressed in the presence of the ATP1-111 mutation. In contrast, CIT2 expression increased in rho+ cells on deletion of COX4. Activation of the retrograde response results in the translocation of the transcription factor Rtg3 from the cytoplasm to the nucleus. Rtg3-GFP translocation to the nucleus was directly observed in rho0 and rho+ cox4Δ cells, but it was blunted in rho0 cells with the ATP1-111 mutation. We conclude that a decrease in MMP is the signal that initiates the retrograde response and leads to increased RLS.